Decolonizzare la lettura. Indecidibilità nella prosa rioplatense (1960-1969) - Lévano, Paulo Fernando (2021)
The paper addresses the issue of conceiving randomness in the process of literary creation by means of outlining a comparative reading of three prose works by J.L. Borges, A. Pizarnik and J. Cortázar. Randomness will be dealt with against the background of intertextuality, a feature that stands out rather provokantly in these authors’ writings. After some preliminary remarks on randomness coming from an epistemological angle, the focus will be set on the way in which these authors randomize the linear path between writer and reader through intertextuality. As a result, a path may be suggested towards the reader reclaiming her role in the construction of literary traditions.